Acoustic pressure and particle motion thresholds in six sciaenid fishes - Horodysky, Andrij Z; Brill, Richard W; Fine, Michael L; Musick, John A; Latour, Robert J (Journal of experimental biology, 2008)
Sciaenid fishes are important models of fish sound production, but investigations into their auditory abilities are limited to acoustic pressure measurements on five species. In this study, we used auditory brainstem response (ABR) to assess the pressure and particle acceleration thresholds of six sciaenid fishes commonly found in Chesapeake Bay, eastern USA: weakfish (Cynoscion regalis), spotted seatrout (Cynoscion nebulosus), Atlantic croaker (Micropogonias undulatus), red drum (Sciaenops ocellatus), spot (Leiostomus xanthurus) and northern kingfish (Menticirrhus saxatilis). Experimental subjects were presented with pure 10 ms tone bursts in 100 Hz steps from 100 Hz to 1.2 kHz using an airborne speaker. Sound stimuli, monitored with a hydrophone and geophone, contained both pressure and particle motion components. Sound pressure and particle acceleration thresholds varied significantly among species and between frequencies; audiograms were notably flatter for acceleration than pressure at low frequencies. Thresholds of species with diverticulae projecting anteriorly from their swim bladders (weakfish, spotted seatrout, and Atlantic croaker) were typically but not significantly lower than those of species lacking such projections (red drum, spot, northern kingfish). Sciaenids were most sensitive at low frequencies that overlap the peak frequencies of their vocalizations. Auditory thresholds of these species were used to estimate idealized propagation distances of sciaenid vocalizations in coastal and estuarine environments.